Perilaku Sosial Pengurus Badan Eksekutif Mahasiswa Dalam Perspektif Etika Berorganisasi di Tingkat Universitas Palangka Raya - Wawan Nopardo Andika Saputra; Eddy Lion; U. Z. Mikdar (Journal Pendidikan Ilmu Pengetahuan Sosial, 2023)
The existence of student organizations in tertiary institutions is important in the context of self-development of students themselves. This is confirmed by the Law of the Republic of Indonesia Number 12 of 2012 concerning Higher Education article 77 concerning Student Organizations. There is an imbalance in the ideal organizational paradigm with field facts, the benefits of participating in the BEM UPR organization, the bargaining value of BEM UPR at the external level, as well as perceptions of BEM UPR's social behavior and organizational ethics, became the basis for researchers interested in studying by taking the title of the final project with the theme of ethics, namely " Social Behavior of Student Executive Board (BEM) Management in the Perspective of Organizational Ethics at the University of Palangka Raya Level. This thesis research aims to analyze the relationship between social behavior patterns of BEM UPR in relation to values and culture in work programs as organizational ethics, as well as educational aspects that can be studied therein. The research design uses qualitative methods with a phenomenological approach. The primary data are people who know in depth the social behavior of BEM Palangka Raya University. While the secondary data is the literature in accordance with the author's research title. Data was collected by observation techniques, interviews, and document collection. The results of the research that the authors obtained were the existence of an ethical culture in organizations. This culture is used for decision making both leaders and members of the organization. Perceptions of the BEM of Palangka Raya University as described in the research results tend to be more positive, because students make their circle of communication in the form of groups. Contextual factors play a role in providing encouragement or motivation for action. In the organizational culture at BEM, University of Palangka Raya, values and norms as important elements can be seen both in real and latent phenomena.